2019
DOI: 10.1080/03601277.2019.1611223
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m older but I can still do this job’: the experiences of mature women in an age-sensitive occupation

Abstract: Title: 'I'm older but I can still do this job': The experiences of mature women in an agesensitive occupation This paper explores how mature female flight attendants [FAs] use Selection, Optimization and Compensation [SOC] strategies to cope with age-related diminishing resources at work. FA is an age-sensitive occupation, and in some organisations, women are under constant pressure to look young and attractive. This Interpretative Phenomenological Analysis study aims to add depth and nuance to our understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…and by being inherently a women's issue, menopause also links to tribal stigma. This triple stigmatization of menopausal women not only violates idealized notions of femininity (Chrisler, 2011;Rowson & Gonzalez-White, 2019;Ussher, 2011) but it also contravenes the hegemonic norm of a reliable and predictable idealized worker (Atkinson et al, 2021;Steffan, 2021). Thus, this may reinforce a perception that menopausal women are not fit for work.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…and by being inherently a women's issue, menopause also links to tribal stigma. This triple stigmatization of menopausal women not only violates idealized notions of femininity (Chrisler, 2011;Rowson & Gonzalez-White, 2019;Ussher, 2011) but it also contravenes the hegemonic norm of a reliable and predictable idealized worker (Atkinson et al, 2021;Steffan, 2021). Thus, this may reinforce a perception that menopausal women are not fit for work.…”
Section: Discussionmentioning
confidence: 95%
“…The focus on cognitive and psychological decline and related unpredictability (e.g., depression, anxiety, irritability, and rage) may be perceived as women's fault or a reflection of their inability to manage themselves, hence reinforcing the “blemish of personal character stigma”; and by being inherently a women's issue, menopause also links to tribal stigma. This triple stigmatization of menopausal women not only violates idealized notions of femininity (Chrisler, 2011; Rowson & Gonzalez‐White, 2019; Ussher, 2011) but it also contravenes the hegemonic norm of a reliable and predictable idealized worker (Atkinson et al., 2021; Steffan, 2021). Thus, this may reinforce a perception that menopausal women are not fit for work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that female airline workers are particularly aware of age-related changes in their physical appearance because appearance is important for their jobs. Thus, considerations of physical changes in this group need to include physical appearance (Rowson and Gonzalez-White, 2019).…”
Section: A Disintegrating Master Narrative Of Older Employeesmentioning
confidence: 99%